Circular Economy: A Network Analysis of the Solid Waste Collection in the City of Rome (Italy) (Journal of Material Science and Technology Research, 2024)
Solid waste management represents a complex issue involving political, socioeconomic, institutional, urbanistic and environmental aspects. Separate collection of waste in the Municipality of Rome is a matter of particular interest due to the size of the city (with an urban area of 1,287 km²) and the considerable amount of waste produced (approximately 1,690,000 tons/year). In this context, this paper proposes an in-depth analysis with the aim of optimizing the delivery of waste to collection centres. The optimization focuses on several key elements, including the strategic distribution of collection centres within the city to make them easily accessible, particularly in densely populated areas or where waste production is higher.Based on the data provided by the Municipality of Rome, the waste materials that should be advantageously recycled as part of the Life Cycle Assessment (LCA) have also been identified. This comprehensive approach can improve the city’s waste management system, promoting the efficient use of resources and reducing environmental impact for greater urban sustainability.